Pore Characterization of Pyrite in the Longmaxi Formation Shale in the Upper Yangtze Area of China - Chen, Xin; Chen, Lei; Tan, Xiucheng; Wang, Chao; Ji, Yubing; Xiong, Min; Wang, Gaoxiang (Frontiers in Earth Science, 2022)
Pyrite is widely distributed in the Longmaxi marine shale in the Upper Yangtze area of China. Pyrite, one of the important components of shale, has an important influence on the enrichment of shale gas. However, there are currently only a few studies on this topic. Based on shale samples from drilling cores using field emission scanning electron microscopy, the pore characteristics of pyrite from the Longmaxi Formation in the Upper Yangtze area of China are studied. The results showed that the intergranular pores of pyrite and abundant organic pores in the organic matter pyrite assemblages are developed in the Longmaxi Formation shale in the study area. Most pyrite framboid pores have triangular or irregular quadrilateral shapes, with pore diameters ranging from 0 to 240 nm. Pores with diameters of 80–240 nm are the major reservoir spaces for shale gas within the pyrite framboids. The average contribution rate of pyrite framboids to shale pores reaches 3.21%, and the highest contribution is 5.66%, indicating that the pyrite pores may have a favorable contribution to the shale reservoir pore system, but the contribution degree is low.